The Lawmaker Role on Concentrations Control: An Analysis of Albanian Market - MoÃ§ka, Ervis; Mehilli, Terida; Demo, Ervin (Richtmann Publishing, 2012)
This paper' search aims to illustrate: the effectiveness of the legislature on market regulation with objective the economicefficiency' and the context within the â€œAuthority of Competition